Natura Pura : On the Recovery of Nature in the Doctrine of Grace. - Long, Steven A. (Moral philosophy and moral theology., 2010)
From speculative theology to the exegesis of Aquinas, to contemporary North American philosophy and Catholic social and ethical thought, to the thought of Benedict XVI, this work argues the crucial importance of the proportionate natural end within the context of grace and supernatural beatitude.